P55 Immunosuppression in the first six weeks following paediatric cardiac transplant - Thomson, Karen; Reinhardt, Zdenka (Archives of disease in childhood, 2020)
AimThe aim of this audit was to establish whether immunosuppression was being prescribed correctly and whether target levels were being reached during the first six weeks post-transplant.1 2MethodThe standards were discussed and agreed, due to an absence of standardised local or national written protocols, with the lead paediatric cardiothoracic transplant consultant and a specialist transplant liaison nurse. The paediatric transplant database provided a list of patients between October 2016 and July 2018, from which paediatric cardiac transplant patients were included in this audit. All data were collected retrospectively, for the first six weeks post-transplant, from patient’s electronic records.ResultsTwenty-three patients were included in the audit; fifteen males and eight females and the mean age was 6 years old. The standards for the timing and dosing of the first ciclosporin dose were met for 87% and 78% of patients respectively. Six patients (26%) had a ciclosporin level within the target range by day 4 post-transplant, for the remaining seventeen patients the average was day 9 post-transplant. The mean levels remained within this range or slightly above after day 9. Azathioprine or mycophenolate was started within 7 days of transplant in 6 patients (23%). Four patients (17%) had documented episodes of rejection; in one patient all other standards were met and in the other three only one additional standard was not met. Nineteen patients (83%) did not have a documented episode of rejection.ConclusionsPost-transplant management is individualised based on multiple factors such as clinical conditions e.g. renal/liver impairment and whether other agents such as ATG or steroids are being used.1 The lack of documentation around the treatment decisions made it difficult to explain deviations from standards in this audit. Ciclosporin standards were not met completely but were most likely unfeasible due to a narrow target range and the time between first dose and level monitoring. There did not appear to be a clear association between standards not being met and episodes of rejection. It would be beneficial to repeat this as a larger, prospective audit using revised standards.ReferencesCostanzo MR, Costanzo MR, Dipchand A, et al. The international society of heart and lung transplantation guidelines for the care of heart transplant recipients. J Heart Lung Transplant 2010;29:914–56.Sandimmun Concentrate for Solution for Infusion 50 mg/ml - Summary of Product Characteristics (SmPC) - (eMC) [Internet]. [cited 2018 Sep 2]. Available from: https://www.medicines.org.uk/emc/product/1036